The Effects of a Physically Active Lifestyle on the Health of Former Professional Football Players - Tuba Melekoğlu; Erdi Sezgin; Ali Işın; Ayşen Türk (MDPI AG, 2019)
The purpose of this investigation was to determine if a physically active lifestyle affects the health of former football players. Sixty former professional football players aged 40–50 years and who ended their sports career at least ten years ago were recruited for the study and grouped into two groups based on their physical activity habits after their retirement. Health and lifestyle characteristics were collected through a questionnaire to obtain information about recreational physical activity levels, diseases, family medical history, smoking, alcohol intake and dietary habits. Furthermore, lung functions, blood parameters and cardiovascular health were evaluated. Our results showed that body weight and body fat percentage were significantly higher in retired footballers who had a sedentary lifestyle compared to those who were physically active. The absolute and predicted values for forced expiratory volume in one-second values were higher in the active group. Twelve retired athletes were found to have intraventricular conduction delay. The findings suggest that former footballers who have higher levels of physical activity have advanced body composition, respiratory functions and serum lipids compared to former footballers with less active lifestyles. It is recommended that former elite athletes should maintain physically active lifestyles to sustain their health and reduce the risk of disease and disability in the later years of life.